Association of handgrip strength with the prevalence of hypertension in a Chinese Han population. Issue 2 (June 2019) - Mallah, Manthar Ali; Liu, Min; Liu, Yu; Xu, Hai-Feng; Wu, Xiao-Jun; Chen, Xiao-Tian; Wang, Hui; Liu, Chun-Lan; Tian, Yuan-Rui; Li, Meng-Xia; Li, Qun; Fu, Jun; et al.
Abstract: Objective: Handgrip strength (HGS) exercise has been reported to reduce blood pressure in both hypertensive and normotensive patients. In this study, we evaluated the association of HGS with hypertension in a Chinese Han Population. Methods: A total of 11, 151 subjects mainly consisting of a rural population were recruited with a multi-stage sampling method in Jurong city, Jiangsu Province, China. Besides hypertension and diabetes, major chronic diseases were excluded. HGS was categorized into tertiles by age and gender. Logistic regression was used to estimate the association of HGS and hypertension with the odds ratio ( OR ) and 95% confidence interval ( CI ). Results: From low to high tertiles of HGS, diastolic blood pressure (DBP) was significantly increased (74.52 ± 7.39, 74.70 ± 7.03, and 75.54 ± 7.01 mmHg, respectively; P trend  = 0.001), as well as in females ( P trend = 0.003). The differences in DBP among the tertiles of HGS were still significant in females even after adjusting for covariates ( P trend = 0.048). No significant differences in systolic blood pressure (SBP) were observed among the tertiles of HGS ( P >0.05). Compared to low HGS, high HGS was significantly associated with hypertension after adjustment for age and gender (adjusted OR, 1.19; 95% CI, 1.06–1.34; P  =0.004). A stratified analysis showed that the significant association of high HGS and hypertension was also observed with the following factors even after adjusting for age and gender: female gender (adjusted OR, 1.25; 95% CI, 1.08–1.46; P =0.004), ages of 60–69 years (adjusted OR, 1.29; 95% CI, 1.06–1.57; P =0.011), and married (adjusted OR, 1.20; 95% CI, 1.06–1.37; P =0.005). However, no significant associations were found after adjusting for age, gender, smoking status, drinking status, body mass index, physical activity level, glucose, high- and low-density lipoprotein cholesterol, total cholesterol, and triglyceride ( P >0.05). Conclusion: The findings of the current study suggest that HGS was positively correlated with DBP in a rural population, and high HGS was associated with hypertension in females; however, the association may be modified by smoking status, drinking status, body mass index, physical activity, cholesterol level, and glucose level. Further utilization of HGS exercises to intervene in the development and prognosis of hypertension should be verified in the future.